2023
DOI: 10.3390/medicina59040645
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Usage in the COVID-19 Intensive Care Unit of an Infectious Diseases Hospital from Nord-Eastern Romania

Abstract: Background and Objectives. The intensive care unit (ICU), especially in an infectious disease hospital, is both an area with a high consumption of antibiotics (atb) and a “reservoir” of multidrug-resistant bacteria. We proposed the analysis of antibiotic therapy practices in such a department that treated, in conditions of a pandemic wave, patients with COVID-19 and its complications. Materials and Methods. This was a retrospective transversal study of 184 COVID-19 patients treated in the ICU of a regional inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…36 Another study of eastern Romania revealed that linezolid were the most prescribed antibiotics (77.2%), while imipenem (75.5%) and ceftriaxone (33.7%) followed by. 37 Several individuals are significantly inclined to develop tiny blood emboli in their lungs as a consequence of COVID-19, which can cause acute respiratory distress syndrome, a symptom of severe COVID-19 diseases, and lead to death. 38 Anticoagulants such as enoxaparin, unfractionated heparin, and rivaroxaban are often given to COVID-19 patients as part of their treatment.…”
Section: Resultsmentioning
confidence: 99%
“…36 Another study of eastern Romania revealed that linezolid were the most prescribed antibiotics (77.2%), while imipenem (75.5%) and ceftriaxone (33.7%) followed by. 37 Several individuals are significantly inclined to develop tiny blood emboli in their lungs as a consequence of COVID-19, which can cause acute respiratory distress syndrome, a symptom of severe COVID-19 diseases, and lead to death. 38 Anticoagulants such as enoxaparin, unfractionated heparin, and rivaroxaban are often given to COVID-19 patients as part of their treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding irrational antibiotic use, the COVID-19 pandemic was not an exception. Several studies have evaluated antibiotic use during the pandemic [29,30]. Vâţă et al conducted a retrospective study to assess antibiotic use practices in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%